2014
DOI: 10.1093/hmg/ddu047
|View full text |Cite
|
Sign up to set email alerts
|

Early and progressive circadian abnormalities in Huntington's disease sheep are unmasked by social environment

Abstract: Insidious changes in behaviour herald the onset of progressive neurodegenerative disorders such as Huntington's disease (HD), sometimes years before overt symptoms are seen. Sleep and circadian disturbances are particularly disruptive symptoms in patients with neurological disorders, but they are difficult to measure in humans. Here we studied circadian behaviour in transgenic HD sheep expressing the full-length human huntingtin protein with an expanded CAG repeat mutation in the juvenile range. Young HD sheep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 40 publications
2
71
0
1
Order By: Relevance
“…The OVT73 sheep display some of the neuropathological changes that occur in HD, including the accumulation of intracellular huntingtin-positive inclusions (18). An alteration in circadian rhythm has been observed, a behavioral phenotype consistent with an early phase in the disease (19). We have also found that levels of specific metabolites are altered in the OVT73 sheep brain and liver.…”
Section: Significancesupporting
confidence: 64%
See 1 more Smart Citation
“…The OVT73 sheep display some of the neuropathological changes that occur in HD, including the accumulation of intracellular huntingtin-positive inclusions (18). An alteration in circadian rhythm has been observed, a behavioral phenotype consistent with an early phase in the disease (19). We have also found that levels of specific metabolites are altered in the OVT73 sheep brain and liver.…”
Section: Significancesupporting
confidence: 64%
“…The OVT73 sheep is the only large animal model that expresses full-length mutant (73 glutamines) human huntingtin (17). The OVT73 sheep are considered a prodromal model system since they display no overt symptoms of the disease or cell loss (19), despite the presence of a recognized pathologic correlate, namely huntingtin-positive aggregates (18), as well as altered metabolite levels (20), and a circadian rhythm disruption measurable by Global Positioning System tracking (19). Comparing urea changes in the postmortem brains of the prodromal OVT73 sheep model and endstage HD individuals, our results also suggest that the urea phenotype may be progressive.…”
Section: Discussionmentioning
confidence: 99%
“…Similar observations were also made in R6/2 mouse model [75] and ovine model of HD [76]. Mutated Htt action and loss of wild-type Htt function affect not only the brain structures, but also peripheral tissues or organ systems like testes, heart, pancreas, skeletal muscle, etc.…”
Section: Telemetrysupporting
confidence: 75%
“…Along with each dataset, the genotype and background strain are available as a spreadsheet and listed on the website. Full details of the animals and the scan sequences used are described in Sawiak et al (2012) and Morton et al (2014). Typical images are shown in Fig.…”
Section: Repository Detailsmentioning
confidence: 99%
“…Recently an ovine model of HD has been assessed with MRI (Morton et al, 2014) and we are currently adding ovine datasets to our online data repository to supplement the mouse data.…”
Section: Introductionmentioning
confidence: 99%